Shear stiffness and damping ratio of unsaturated soil - Wong, Kah Chou. (2013)
In geotechnical practice, unsaturated soil condition is commonly encountered. Both shear stiffness and damping ratio are the fundamental parameters for dynamic study in geotechnical engineering. These have garnered more interest in the research to determine dynamic soil properties using laboratory tests like the small strain shear modulus (Gmax), Young's modulus (Emax) and the damping ratio (ξ). In this project, the effect of the saturation on shear stiffness and damping ratio of the soil will be investigated.